(untitled) (The Research of Medical Science Review, 2025)
Background: Diabetic nephropathy is a leading cause of chronic kidney disease in type II diabetics.Serum creatinine, though widely used, has limitations due to its dependence on muscle mass.Cystatin C offers a more accurate and independent measure of glomerular filtration rate (GFR).This study evaluates the diagnostic accuracy of Cystatin C compared to creatinine-based estimations. Objective:To compare the diagnostic accuracy of Cystatin C with serum creatinine for estimation of glomerular filtration rate (GFR) in type II diabetic patients using the CKD-EPI equation as the reference standard.Methodology:This hospital- based, cross-sectional study was done in the department of Chemical Pathology, Bahawal Victoria Hospital, Bahawalpur; conducted over six months following CPSP approval.A total of 100 type II diabetic patients aged 20–60 years were enrolled. Serum levels of Cystatin C and creatinine were measured. GFR was estimated using the CKD-EPI equations for both markers. Diagnostic accuracy was assessed using sensitivity, specificity, PPV, NPV, and ROC analysis.Results:In this study involving 100 patients with type II diabetes mellitus, Cystatin C demonstrated a sensitivity of 64.2% in correctly identifying individuals with impaired glomerular filtration rate (GFR), and a specificity of 85.1% in identifying those with normal renal function when compared to the CKD-EPI creatinine-based gold standard. The positive predictive value (PPV) was 78.3%, indicating a high likelihood that individuals testing positive with Cystatin C truly had impaired GFR. The negative predictive value (NPV) was 74.2%, suggesting a moderate probability of ruling out renal impairment in Cystatin C- negative cases. The area under the ROC curve (AUC) was 0.77, reflecting a moderate level of diagnostic accuracy. These results underscore the potential utility of Cystatin C as a screening and diagnostic tool for early renal dysfunction, particularly in a high-risk diabetic population. Conclusion:The findings of this study support the use of Cystatin C as a reliable and effective biomarker for estimating glomerular filtration rate (GFR) in patients with type II diabetes mellitus. Unlike serum creatinine, Cystatin C is less influenced by confounding variables such as muscle mass, age, or gender, making it a more stable and specific indicator of kidney function. While it may not completely replace creatinine in all settings, its moderate sensitivity, high specificity, and overall diagnostic value (AUC = 0.77) suggest that it can serve as a valuable adjunctive tool in the early detection and management of diabetic kidney disease. Incorporating Cystatin C testing into routine clinical practice may lead to earlier diagnosis, better risk stratification, and timely interventions, ultimately improving patient outcomes.